The Continuity of Qur'anic Exegesis in Sumatra: A Study of Abdrurrauf Singkel, HAKA, and HAMKA within the Local Islamic Tradition - Fahmi Akhyar Al Farabi; Abdur Rohman; Saiful Amin; Muhammad Thoriqul Islam; Muhamad Shofwan Muttaqin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The development of Qur’anic exegesis in Sumatra illustrates a continuous intellectual trajectory linking classical, transitional, and modern phases of Islamic scholarship. This study examines three major exegetes—Abdurrauf al-Sinkili, Haji Abdul Karim Amrullah (HAKA), and Haji Abdul Malik Karim Amrullah (HAMKA)—by exploring their biographical contexts, socio-historical settings, and distinctive interpretive features. Abdurrauf, through Tafsir Tarjuman al-Mustafid (17th-century Aceh), introduced an ijmālī and Sufi-oriented approach to make the Qur’an accessible to Malay audiences. HAKA’s Tafsir al-Burhan reflects early 20th-century Minangkabau reformism, employing a taḥlīlī method emphasizing reason and social engagement. Meanwhile, HAMKA’s Tafsir al-Azhar represents a modern, comprehensive synthesis that integrates transmitted and rational interpretations while addressing contemporary socio-political realities. Read through Talal Asad’s concept of Islam as a discursive tradition and John Bowen’s Muslims through Discourse, these tafsir works reveal not only textual interpretation but also ongoing negotiations of authority, identity, and social ethics. The continuity of Sumatra’s tafsir tradition thus reflects a discursive evolution, demonstrating how local scholars reinterpret the Qur’an in response to shifting historical and political contexts. The novelty of this study lies in positioning Nusantara tafsir as a dynamic dialogical model that contributes to contemporary Muslim societies by bridging classical heritage, local culture, and modern intellectual demands.